2015
DOI: 10.1093/ntr/ntu249
|View full text |Cite
|
Sign up to set email alerts
|

Systematic and Meta-Analytic Review of Research Examining the Impact of Menstrual Cycle Phase and Ovarian Hormones on Smoking and Cessation

Abstract: Introduction: To determine the effect of ovarian hormones on smoking, we conducted a systematic review of menstrual cycle effects on smoking (i.e., ad lib smoking, smoking topography, and subjective effects) and cessation-related behaviors (i.e., cessation, withdrawal, tonic craving, and cue-induced craving). Methods: Thirty-six papers were identified on MEDLINE that included a menstrual-related search term (e.g., menstrual cycle, ovarian hormones), a smoking-related search term (e.g., smoking, nicotine), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 92 publications
(152 reference statements)
3
64
0
Order By: Relevance
“…Further, while the analyses were adjusted for mood disorders, premenstrual dysphoric disorder (PMDD) was not assessed by the AUDADIS-IV. Withdrawal symptoms overlap with premenstrual symptoms (Allen et al, 2000) and changes in ovarian hormones are associated with differences in a range of smoking behaviors including withdrawal (see Weinberger et al, 2015 for a review). Additional research is needed to understand the role of PMDD in the relationship between withdrawal symptoms and smoking cessation for women.…”
Section: Discussionmentioning
confidence: 99%
“…Further, while the analyses were adjusted for mood disorders, premenstrual dysphoric disorder (PMDD) was not assessed by the AUDADIS-IV. Withdrawal symptoms overlap with premenstrual symptoms (Allen et al, 2000) and changes in ovarian hormones are associated with differences in a range of smoking behaviors including withdrawal (see Weinberger et al, 2015 for a review). Additional research is needed to understand the role of PMDD in the relationship between withdrawal symptoms and smoking cessation for women.…”
Section: Discussionmentioning
confidence: 99%
“…We also have not accounted for menstrual status and menstrual cycle phase, which might alter smoking habits and relapses after abstinence (56, 57). …”
Section: Discussionmentioning
confidence: 99%
“…For smoking cessation, greater withdrawal has been observed in human females during the luteal phase (O'Hara et al, 1989). In a recent meta-analysis of smoking cessation studies, greater withdrawal was found during the luteal phase compared with the follicular phase (Weinberger et al, 2015). Thus, the reduced subjective effect of nicotine during the luteal phase may contribute to less saliency of nicotine-related cues, but that does not necessarily correspond to reduced withdrawal symptoms.…”
Section: Effects Of Hormones During the Reproductive Cycle In Femamentioning
confidence: 99%